Evaluating a stroke-specific version of the Illness Perception Questionnaire-Revised, using the Think-Aloud method - Aujla, Navneet; Vedhara, Kavita; Walker, Marion; Sprigg, Nikola (SAGE Publications, 2018)
The main purpose was to evaluate, using the Think-Aloud method, a version of the Illness Perception Questionnaire-Revised (IPQ-R) for stroke survivors (the Stroke IPQ-R). Six stroke survivors (mean age=58.8 years, range=31 to 78 years, SD=18.9 years) took part in Think-Aloud interviews, analysed according to established guidelines. Overall, 179 problems emerged. The most noteworthy was missing or insufficient Think-Aloud data generated, where participants did not think out loud. Others included complex and negative item wording, and items on the treatment control sub-scale. Questionnaire length, simpler wording and verbal probing are important considerations in further development of an IPQ-R for stroke.